Amyloid-like aggregation of ovalbumin: Effect of disulfide reduction and other egg white proteins. (December 2016) - Jansens, Koen J.A.; Brijs, Kristof; Delcour, Jan A.; Scanlon, Martin G.
Abstract: During heating of ovalbumin, the major protein of chicken egg white, amyloid-like aggregates are formed. Process conditions, redox agents and the presence of other proteins affect the specific nature of amyloid formation. In this work, amyloid formation of ovalbumin was investigated using a combination of fluorescence measurements, dynamic light scattering and ultrasound measurements. Fluorescence measurements indicated more pronounced conformational changes upon heating (60–80 °C) in the presence of the reducing agent dithiothreitol, whereas the oxidizing agent potassium iodate had little to no effect. Also particle size after heating was larger when disulfide bonds were reduced. Large particles were formed when ovalbumin was heated in the presence of other egg white proteins and also the pattern of change in ultrasound properties of ovalbumin-egg white mixtures was affected by these other egg white proteins. Changes in ultrasonic velocity and attenuation showed that amyloid formation in ovalbumin depends on the molecule's disulfide bond, and it is postulated that the amyloid-like aggregates formed as a result of thermal treatment are composed of a compact core surrounded by loosely packed protein segments. Graphical abstract: Highlights: Heating of the egg white protein ovalbumin led to amyloid-like aggregates. Changes in ultrasonic velocity and attenuation occurred during amyloid formation. The disulfide bond strongly affected the thermally-induced volumetric transitions. The changes in ultrasonic properties also depended on other egg white proteins. It is postulated that amyloid-like ovalbumin aggregates consist of a compact core.